Lithofacies And Depositional Analysis Environment Of West Section Kolok Nan Tuo Village, Sawahlunto City, West Of Sumatera - Cahyaningsih, Catur; Ritonga, Anjas Latif; Aldila, Shaury; Zulhikmah, Zulhikmah (UIR PRESS, 2018)
Research areas were located in the west of Kolok Nan Tuo Village. Geographically this area is located at coordinates 00 ° 36'57,85 '' - 00 ° 37'56,89 '' latitude and 100 ° 42'10,08 '' 100 ° 43'47,28